Quantitative imaging of acoustic reflection and interference. (29th January 2015) - Malkin, Robert; Todd, Thomas; Robert, Daniel
Abstract: This paper presents a method for time resolved quantitative imaging of acoustic waves. We present the theoretical background, the experimental method and the comparison between experimental and numerical reconstructions of acoustic reflection and interference. Laser Doppler vibrometry is used to detect the modulation of the propagation velocity of light, c, due to pressure-dependant changes in the refractive index of air. Variation in c is known to be proportional to variation in acoustic pressure and thus can be used to quantify sound pressure fluctuations. The method requires the laser beam to travel through the sound field, in effect integrating pressure along a transect line. We investigate the applicability of the method, in particular the effect of the geometry of the sound radiator on line integration. Both experimental and finite element reconstructions of the sound field are in good agreement, corroborating punctual pressure measurements from a precision microphone. Spatial limitations and accuracy of the method are presented and discussed.